Simultaneous skin friction and velocity measurements in high Reynolds number pipe and boundary layer flows. (25th July 2019) - Baidya, R.; Baars, W. J.; Zimmerman, S.; Samie, M.; Hearst, R. J.; Dogan, E.; Mascotelli, L.; Zheng, X.; Bellani, G.; Talamelli, A.; Ganapathisubramani, B.; Hutchins, N.; et al.
Abstract : Streamwise velocity and wall-shear stress are acquired simultaneously with a hot-wire and an array of azimuthal/spanwise-spaced skin friction sensors in large-scale pipe and boundary layer flow facilities at high Reynolds numbers. These allow for a correlation analysis on a per-scale basis between the velocity and reference skin friction signals to reveal which velocity-based turbulent motions are stochastically coherent with turbulent skin friction. In the logarithmic region, the wall-attached structures in both the pipe and boundary layers show evidence of self-similarity, and the range of scales over which the self-similarity is observed decreases with an increasing azimuthal/spanwise offset between the velocity and the reference skin friction signals. The present empirical observations support the existence of a self-similar range of wall-attached turbulence, which in turn are used to extend the model of Baars et al. ( J. Fluid Mech., vol. 823, p. R2) to include the azimuthal/spanwise trends. Furthermore, the region where the self-similarity is observed correspond with the wall height where the mean momentum equation formally admits a self-similar invariant form, and simultaneously where the mean and variance profiles of the streamwise velocity exhibit logarithmic dependence. The experimental observations suggest that the self-similar wall-attached structures follow an aspect ratio of 7:1:1 in the streamwise, spanwise and wall-normal directions, respectively.